Reduced Erg Dosage Impairs Survival of Hematopoietic Stem and Progenitor Cells. (24th April 2017) - Xie, Ying; Koch, Mia Lee; Zhang, Xin; Hamblen, Melanie J.; Godinho, Frank J.; Fujiwara, Yuko; Xie, Huafeng; Klusmann, Jan-Henning; Orkin, Stuart H.; Li, Zhe
Abstract : ERG, an ETS family transcription factor frequently overexpressed in human leukemia, has been implicated as a key regulator of hematopoietic stem cells. However, how ERG controls normal hematopoiesis, particularly at the stem and progenitor cell level, and how it contributes to leukemogenesis remain incompletely understood. Using homologous recombination, we generated an Erg knockdown allele ( Erg kd ) in which Erg expression can be conditionally restored by Cre recombinase. Erg kd/kd animals die at E10.5–E11.5 due to defects in endothelial and hematopoietic cells, but can be completely rescued by Tie2-Cre -mediated restoration of Erg in these cells. In Erg kd/+ mice, ∼40% reduction in Erg dosage perturbs both fetal liver and bone marrow hematopoiesis by reducing the numbers of Lin – Sca-1 + c-Kit + (LSK) hematopoietic stem and progenitor cells (HSPCs) and megakaryocytic progenitors. By genetic mosaic analysis, we find that Erg -restored HSPCs outcompete Erg kd/+ HSPCs for contribution to adult hematopoiesis in vivo. This defect is in part due to increased apoptosis of HSPCs with reduced Erg dosage, a phenotype that becomes more drastic during 5-FU-induced stress hematopoiesis. Expression analysis reveals that reduced Erg expression leads to changes in expression of a subset of ERG target genes involved in regulating survival of HSPCs, including increased expression of a pro-apoptotic regulator Bcl2l11 ( Bim ) and reduced expression of Jun . Collectively, our data demonstrate that ERG controls survival of HSPCs, a property that may be used by leukemic cells.